Scopoletin: Anticancer potential and mechanism of action - Lia Meilawati; Rita Marleta Dewi; Aprilia Nur Tasfiyati; Abdi Wira Septama; Lucia Dwi Antika (Asian Pacific Journal of Tropical Biomedicine, 2023)
Cancer is considered a leading cause of death worldwide due to its high morbidity and mortality rate. Conventional treatments for cancer therapy, such as chemotherapy, and radiotherapy, have been hampered by their side effects. Natural product-derived plants have been used for decades to treat diseases. Compared to conventional therapy, natural product has the potential to be effective against cancer with fewer side effects. This current review discussed the potential of scopoletin, a coumarin present in many edible plants, which elicits anticancer properties through multiple mechanisms, including modulating cell cycle arrest, inducing apoptosis, and regulating multiple signaling pathways. Understanding these mechanisms highlights the potential of scopoletin as a candidate for chemoprevention and chemotherapy.